Crystal structure of hyoscyamine sulfate monohydrate, (C17H24NO3)2(SO4)(H2O). Issue 4 (December 2020) - Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of hyoscyamine sulfate monohydrate has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Hyoscyamine sulfate monohydrate crystallizes in space group P 21 (#4) with a = 6.60196(2), b = 12.95496(3), c = 20.93090(8) Å, β = 94.8839(2)°, V = 1783.680(5) Å 3, and Z = 2. Despite the traditional description as a dihydrate, hyoscyamine sulfate crystallizes as a monohydrate. The two independent hyoscyamine cations have different conformations, which have similar energies. One of the cations is close to the minimum-energy conformation. Each of the protonated nitrogen atoms in the cations acts as a donor to the sulfate anion. The hydroxyl group of one cation acts as a donor to the sulfate anion, while the hydroxyl group of the other cation acts as a donor to the water molecule. The water molecule acts as a donor to two different sulfate anions. The cations and anions are linked by complex chains of hydrogen bonds along the a -axis. The powder pattern has been submitted for inclusion in the Powder Diffraction File™ (PDF®).